Ameliorating the Poor Dissolution Rate of Selexipag in Aqueous Acidic Conditions Following Confinement into Mesoporous Silica - Attia, Mohamed S.; Ghazy, Fakhr-Eldin S. (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Pulmonary Arterial Hypertension (PAH) is a serious condition with available treatment options, including Selexipag (SXP), a selective prostacyclin receptor agonist that has effectively reduced patient morbidity and mortality. SXP is limited by poor water solubility, especially in acidic solutions, which can affect its bioavailability and therapeutic efficacy. Therefore, strategies to tackle the solubility of SXP, such as nano-based Drug Delivery Systems (DDSs), should be explored. Objectives: The study aimed to tackle the poor dissolution rate of SXP and, consequently, improving the clinical efficacy and treatment outcomes of PAH patients. Materials and Methods: Three forms of Mesoporous Silica Nanoparticles (MSNs) were investigated as a DDS. SXP was loaded to MSNs (SBA-15, MCM-41, and KIT-6) via rotary evaporation technique and characterized for in vitro dissolution rates, drug release kinetics, morphology, crystallinity, interaction and surface properties. Results and Conclusion: Incorporating SXP as a monolayer to SBA-15 formulations significantly improved its dissolution rate, achieving an enhancement ratio of 9.48 at pH 1.2 compared to the pure drug. Notably, the monolayer and double-layer-loaded SBA-15 formulations exhibited the highest dissolution efficiency percentages, with values of 72.85% and 69.01%, respectively, surpassing that of raw SXP. The entrapment of SXP within SBA-15 mesopores was evident from pore volume reduction. The enhancement in dissolution rates was ascribed to the conversion of SXP into an amorphous state upon confinement within the nanostructure, which was indicated through X-ray diffraction and scanning electron microscopy analyses.
Keywords: Mesoporous silica; Drug dissolution; Selexipag; Solubility; Pulmonary arterial hypertension; Crystallinity